A longitudinal study on the prevalence of iron deficiency anemia in the multiethnic communities of Jhargram, West Bengal - Mandal, Moumi; Mishra, Niladri Prasad; Chatterjee, Poulomi; Bhattacharyya, Sanchari; Mondal, Keshab Chandra; Acharya, Sagar (Acta Biologica Szegediensis, 2023)
Anemia is a significant public health concern in India, with an esti-mated prevalence of 38% to 82% in non-pregnant females and 18% to 59% in males. Destitution, poor nutrition, illiteracy, unhealthy practices, obliviousness, and inadequate health service is the significant reasons for the higher rate of IDA in the tribals of India. The objective of the present study was to estimate the disease burden in Binpur-I and II, Jhargram blocks in West Bengal, India. The research was planned as a multiethnic community-based investigation that includes age and sex-specific gradation of anemia with iron status (SF, SI, TIBC). 910 participants (female: 529 and male: 381) were enrolled in the study. Overall, 67.47% of individuals were diagnosed with anemia (female: 42.74% and male: 24.73% ). According to severity, 29.12%, 27.14%, and 11.2% of individuals were moderate, mild, and severely anemic. Results also showed that IDA is prevalent among all age groups irrespective of sex, with the highest rates in the 40.1 - 60 age group (female). The higher prevalence of the geriatric population could be due to chronic disease, iron deficiency, and genetic polymorphisms, which require future investigations.